Enhancing Security Metrics and Energy-Efficient Cryptographic Techniques for IoT-Enabled Smart Cities and Wearable Device - Singh, Manish Kumar; Kumar, Rohit (International Journal of Computer Sciences and Engineering, 2025)
The proliferation of Internet of Things (IoT) devices in smart cities and wearable technologies has introduced significant challenges in ensuring robust security while maintaining energy efficiency. This paper presents an advanced framework that integrates novel security metrics with energy-efficient cryptographic techniques tailored for resource- constrained IoT devices. We introduce the Unified Power-Resource Index (UPRI), a comprehensive metric that evaluates the trade-off between security strength and energy consumption. Through extensive simulations and real-world deployments, we demonstrate the efficacy of our proposed methods in enhancing security without compromising energy efficiency. The results indicate a substantial improvement in performance metrics, offering a scalable solution for future IoT applications. This study contributes to the ongoing efforts to develop secure and sustainable IoT ecosystems in smart cities.